Identificación y análisis de la definición de éxito en gerencia de proyectos, una Revisión Sistemática de Literatura (RSL) (2017)
This degree work is the result of an investigation about the definition of success in project management through a Systematic Literature Review (SLR). In the first place, is presented the methodology for the RSL, which contains the research questions. Subsequently, the results of the research are presented, where it’s evident the importance of defining the success of project management and differentiating it from the success of the project, as well as the evolution of the definition of success in project management from 1900 to May 2017 and the relation with the industry according to different authors and institutions internationally recognized. Finally, is presented the future work proposed by different authors about project management success. Based on the results obtained, are given in terms of success factors, that is the way to achieve success in the management. For this reason, a definition of success in project management it’s proposed integrating the meaning of the main elements of it, in order to guide the efforts of the project managers and to contribute to the increase of the success in the project management.